Mothers' Attitude about Treatment and Prevention of Diarrhea in Children Under Five Years at the Eastern AL Hamza city - Mohammed Jameel Wahab, Selman Hussain Faris, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: This study aimed to evaluate Mothers’ Attitude about Treatment and Prevention of Diarrhea in Children Under Five Years. Methodology: The study was descriptive using quantitative data collection method. In which assessment approach is applied to achieve the objectives of the study and was conducted during the period of the study from October 25th 2021 to March 1st 2022. Results: The study findings showed that (63.2%) of mothers had negative attitude regarding the treatment and prevention of diarrhea and (36.8%) only of them had positive attitude. Conclusion: Most mothers’ had negative attitude about prevention and home management of diarrhea in children under five years..